Analysis of individual, contextual and organisational factors on money laundering risk in banking institutions: a behavioural judgement approach / Yusarina Mat Isa - Mat Isa, Yusarina (2019)
In recent years, various incidences of money laundering cases involving banking institutions as a conduit have surfaced even more concern over money laundering risk judgement. Despite the increased attention on money laundering risk, there are limited studies that look at the behavioural perspective of the money laundering risk judgement. Based on behavioural decision theory, Bonners' judgement and decision making framework and modified Simon's model for money laundering risk assessment, this study aims to address the above gap by examining the behavioural factors (which are classified into three dimensions - individual, contextual and organisational factors) that could influence money laundering risk judgement. To provide a holistic viewpoint on money laundering risk judgement, this study is designed into two sub-studies, denoted as Study One and Study Two which utilizes survey and between-within-subjects experimental method respectively. The combination of these two sub-studies is designed in such a way to provide robust findings to answer the questions of to what extent do the individual, contextual and organisational factors affect money laundering risk judgement and how do these individual, contextual and organisational factors intervene and interact, given the circumstances surrounding money laundering risk judgement. Drawing upon 165 and 185 cleaned responses for Study One and Study Two respectively, the data were analysed using Partial Least Squares of Structural Equation Modelling. For Study One, examination on the antecedent factors that could influence money laundering risk judgement reveals that individual factor (i.e. competency) as the anchor element within a person, is significant in influencing money laundering risk judgement either in its direct or indirect capacity. Study One also demonstrates that contextual factor (i.e. risk consciousness) mediates some of the relationships between competency and money laundering risk judgement. For the organisational factor (i.e. internal controls), Study One provides evidence of moderation effect on the relationship between competency and money laundering risk judgement. Study Two, which experimentally examine the factors influencing money laundering risk judgement in a controlled setting, corroborates the findings of Study One in confirming the indirect effect of individual factor (i.e. competency) on money laundering risk judgement. Study Two also provide further evidence that show the existence of mediation effect of contextual factor (i.e. CDD task intensity) and moderation effect of organisational factor (i.e. regulatory supervision) on the relationship between competency and money laundering risk judgement. For a less explored area in the study of behavioural judgement, this thesis provides significant contributions in confirming the theoretical foundations underlying behavioural judgement as well as adds value to the existing body of knowledge on money laundering risk judgement. Extending the study on behavioural judgement to a vastly different landscape in the context of money laundering risk in the banking institutions is hoped to set a new branch of research in the related areas. The theoretical foundation framed by this study could provide inputs for future studies by the academicians. Practically, the findings could offer a solid framework for the banking institutions and relevant regulators in improving money laundering risk management with enhanced understanding on the behaviours of the bank officers. The added knowldege on money laundering risk provided by this thesis could also benefit other stakeholders such as potential inventors, shareholders and auditors in advancing their understanding towards the conduct of the banking institutions in managing money laundering risk.